(untitled) (The Journal of Interdisciplinary Human Studies, 2025)
The article analyzes the formation and development of Sufi Qur’anic exegesis and its esoteric (ishari) interpretations based on historical sources. The study examines Najm al-Din Kubra’s Ta’wilat Najmiyya, the esoteric commentaries continued by Simnani, as well as the methods of Qashani and other prominent Sufi exegetes through a comparative approach. It also discusses the theoretical foundations of ishari exegesis, the emergence of symbolic interpretation, and its influence on later generations of Sufi commentators. The article further investigates major Persian and Arabic Sufi tafsirs produced in the region of Mawarannahr, including Khoja Porsa’s Tafsiri Qur’on and Charxi’ Tafsiri Charxi. Their manuscript copies, structure, stylistic features, and significance within the tradition of Sufi Qur’anic interpretation are examined in detail. The findings show that ishari tafsirs first emerged within oral traditions and later developed into independent written works. Their primary aim was to interpret the inner meanings of Qur’anic verses in harmony with spiritual and ethical principles. The conclusion emphasizes the importance of Sufi tafsirs as a distinct school within Qur’anic interpretation, their impact on later exegetes, and their enduring scholarly value.